Effect of broiler breeder's body weight after induced molting by zinc oxide on egg production, fertility, hatchability and chicks weight - Ali, Khasraw Abdulla (Sulaimani Journal for Pure and Applied Sciences, 2016)
This study investigates the effect of different body weight of Arbor Acres broiler breeder hens after molting on product performance. 296 hens, the birds were molted by zinc oxide with or without supplementation of vitamin C and the body weight of the birds after molting at 361 days old of age, were randomly divided into eight treatments (T‎) of body weight: [T1(3.783), T2(3.714),T3( 3.458), T4(3.428), T5(3.380),T6( 3.318), T7(3.276) and T8(3.253) ±50]. Weekly eggs/hen, hen day production and egg mass revealed significant (p<0.05) differences between different body weights of hens. Hens in molting significantly had higher values of these traits compared with non-molting hens. Effect of body weight on Fertility percentage of eggs did not differ while hatchability of fertile eggs and hatchability of total eggs affected by the different treatments with the superiority of molting treatments on non-molting treatments. Results show no significant effect of body weight on egg weight and chick’s weight.
Keywords: Broiler breeder; Body weight; Induced Molting; Hatchability; Fertility